Kinetic response of conformational variation of duck liver globular protein to ultrasonic stimulation and its impact on the binding behavior of n-alkenals. (October 2021) - Xu, Le; Zheng, Yuanrong; Zhou, Changyu; Pan, Daodong; Geng, Fang; Cao, Jinxuan; Xia, Qiang
Abstract: This work investigated the effects of low-frequency ultrasound (US) induced conformational variation of duck liver globular proteins (DLGPs) on the binding behavior of n -alkenals based on multi-spectroscopic analysis combined with headspace solid phase microextraction technique. Results suggested that US-treatments, with the frequency of 40 kHz and the power density of 26.7 W/L, induced obvious tertiary and quaternary structure changes of DLGPs, as revealed by fluorescence and ultraviolet–visible absorption spectroscopy, whereas the secondary and primary structures of DLGPs remained almost unaffected, suggesting the presence of molten-globule (MG) intermediates due to US-treatment. Meanwhile, the particles size and absolute values of ζ-potential exhibited significant increases as the functions of ultrasonic durations. According to multivariate results, the conformational variations, involving natural, MG and post-MG states, could be differentiated successfully. The US-induced conformational changes of DGLPs allowed it easier to interact with volatile n -alkenals, attributed to the enhanced hydrophobic interaction and covalent binding. Correspondingly, the headspace fractions of n -alkenals were greatly reduced after ultrasound pretreatments, with different degrees ranging from 5.61 to 59.39%, depending on chemical structures and processing conditions. This work suggests the great potential of specific conformational variations of DLGPs induced by ultrasonic pretreatments to modulate flavor features of protein-based products. Highlights: The kinetics of ultrasound (US)-induced conformational changes were characterized. The induced flexible structures by US could be identified by multivariate methods. US markedly enhanced the interaction process between alkenals and DLGPs. Hydrophobic interaction and Michael addition potentially dominated in alkenals-DLGPs binding. Alkenals-DLGPs interaction process can be confirmed by fluorescence quenching.